Pathological Evaluation of Canine Hepatic Cirrhosis and Necro-inflammatory Activity - Shahad Saad Mahdi; Jihad Abdulameer Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Hepatic fibrosis is a common pathological result of chronic liver diseases, which is a dynamicprocess of liver decomposition mediated by cellular mediators in response to injury.Objective: The present study aims to evaluate the histopathological features of dog-liver fibrosis and / orcirrhosis.Materials and Methods: 40 liver samples were collected; 12 liver fibrosis suspected animals were performedthe histopathology to determine the main features of canine liver fibrosis.Results: The histopathology revealed chronic hepatitis with liver islands separated by strips of fibroblastsand collagen, moderate numbers of macrophages, lymphocytes and plasma cells. Also in fibrosis betweenchronic hepatitis/cirrhosis had a wide range of severity and inflammation was observed primarily aroundfibrous tissue or was surrounded by fibrous tissue but extended to the liver parenchyma. The histochemicalstudy revealed to a deposition of collagen fibers in the portal, subscapular and interlobular regions.Conclusion: The histopathology revealed a range of lesions vary from mild hepatic degenerative changes tosevere fibrotic features associated with canine hepatic fibrosis and early cirrhosis.